Hotspot of Organic Carbon Export Driven by Mesoscale Eddies in the Slope Region of the Northern South China Sea - Zhang, Miao; Wu, Ying; Wang, Fuqiang; Xu, Dongfeng; Liu, Sumei; Zhou, Meng (Frontiers in Marine Science, 2020)
Mesoscale eddies frequently observed in the northern slope region of the South China Sea significantly modulate the biological and biogeochemical behavior of organic carbon. There have been few comparative studies on biological and biogeochemical processes in a pair of anticyclonic and cyclonic eddies (ACEs and CEs) in continental slope. In our research, an ACE-CE pair was observed in June 2015 on the northern slope of the SCS. The surface dissolved organic carbon (DOC) was approximately 3 μmol L-1 higher in the ACE than that of the CE, and particulate organic carbon (POC) was approximately 3.9 μmol L-1 higher in the CE than in the ACE. Along the transect across the ACE and CE, the concentrations of DOC and fluorescent dissolved organic matter (FDOM) were lower in ACE region than those of the CE region, which were coincident with the downwelling and upwelling in the eddies. In the euphotic layer, the total organic carbon (TOC) stock in the ACE was higher than that of the CE with a lower POC/TOC ratio. There was net consumption of both DOC and POC in the upper 120 m in the ACE; however, net POC production was observed within the CE. The results also indicate that the production of fresh organic carbon was higher in the CE while carbon export was higher in ACE. The vertical export rate of DOC and POC at 120 m in the ACE were approximately 70.2 and 1.69 mmol C m-2 d-1. Summarizing these measurements, the horizontal export of TOC across the slope to the SCS basin transported by dual eddies is estimated more than 22.1 × 109 g C. This estimate implies that mesoscale eddies can contribute significantly to carbon sequestration in the SCS.